Peran Majlis Ta'lim Al-Muttaqun dalam Meningkatkan Pemahaman Keagamaan Masyarakat pada Kajian Fiqih Ibadah di Desa Bungtiang Kecamatan Sakra Barat - Hanafi, Muhammad; Jumatriadi, Jumatriadi; Azhari, M. Rozi (PALAPA, 2024)
This study aims to examine the role of Majelis Ta’lim Al-Muttaqun in enhancing the community’s religious understanding, particularly in the aspect of fiqih ibadah in Bungtiang Village, Sakra Barat District. The main focus is to analyze the contribution of the majelis ta’lim to improving the community’s understanding of daily worship practices and to identify supporting and inhibiting factors in the learning process. This study employs a qualitative descriptive approach, with data collected through participant observation, in-depth interviews, focus group discussions (FGDs), and documentation. The research informants consist of religious leaders, majelis ta’lim participants, community leaders, and academics relevant to the study of fiqih ibadah. The findings indicate that Majelis Ta’lim Al-Muttaqun plays a significant role as an effective medium for religious learning by delivering fiqih ibadah materials that are adapted to the community’s level of understanding. Supporting factors include the active involvement of preachers, the availability of relevant teaching materials, and the high level of religious enthusiasm among community members, while inhibiting factors comprise participants’ limited time, a lack of variety in teaching methods, and low religious literacy among some segments of the community. The study concludes that the presence of the majelis ta’lim provides a positive contribution to enhancing understanding of fiqih ibadah; however, optimization of learning strategies and strengthened institutional support remain necessary to broaden its impact on the development of the community’s religious understanding.